DAPSONE RESISTANCE IN A Mycobacterium leprae ISOLATE WITH TWO POINT MUTATIONS IN folP GENE FROM A LEPROSY PATIENT - Ardiaty, Dinar; Wahyuni, Ratna; Prakoeswa, Cita; Abdullah, Rasyidin; Agusni, Indropo; Izumi, Shinzo (Institute of Topical Disease Universitas Airlangga, 2012)
Drug resistance in leprosy is important for Leprosy Control Program, since the WHO-Multidrug regiment (MDT) has been used for global treatment of leprosy for more than two decades already. A Dapsone resistance case in a Multibacillary (MB) leprosy case is reported. The patient was diagnosed and treated in Tajuddin Chalid Hospital Makassar, South Sulawesi. Previously he was treated in a health center at South Sulawesi and was given a treatment for one year, before referred to the hospital. The leprosy skin lesions are still active with erythematous skin lesions and thickened ear lobe. Bacteriological examination was positive for Acid Fast Bacilli, the Bacterial Index was 3+ and the Morphological Index was 1%. The specimens of M.leprae isolation was sent to the Institute of Tropical Disease Surabaya for drug resistance study. Using the Lp1-2 and Lp3-4 nested primers, PCR test was positive for M.leprae.Sequencing result for folP gene showed a double mutation at codon 53 (ACC / Threonin ) which become (AGG / Arginine). Simultaneous mutation at two nucleotides at one codon has never been reported in Indonesia before and this phenomenon is important for leprosy control policy.